A G(enomic)P(ositioning)S(ystem) for Plant RNAPII Transcription. (August 2020) - Leng, Xueyuan; Thomas, Quentin; Rasmussen, Simon Horskjær; Marquardt, Sebastian
Abstract : Post-translational modifications (PTMs) of histone residues shape the landscape of gene expression by modulating the dynamic process of RNA polymerase II (RNAPII) transcription. The contribution of particular histone modifications to the definition of distinct RNAPII transcription stages remains poorly characterized in plants. Chromatin immunoprecipitation combined with next-generation sequencing (ChIP-seq) resolves the genomic distribution of histone modifications. Here, we review histone PTM ChIP-seq data in Arabidopsis thaliana and find support for a Genomic Positioning System (GPS) that guides RNAPII transcription. We review the roles of histone PTM 'readers', 'writers', and 'erasers', with a focus on the regulation of gene expression and biological functions in plants. The distinct functions of RNAPII transcription during the plant transcription cycle may rely, in part, on the characteristic histone PTM profiles that distinguish transcription stages. Highlights: PTMs of histone residues affect gene expression by defining transcription stages. ChIP-seq reveals the distribution of histone PTMs during transcription. A GPS based on the distribution profile of histone PTMs and histone variants underlies RNAPII transcription stages in plants. Misalignment of GPS and transcription units suggests novel transcription activity and regulation. Histone PTM reader, writer, and eraser enzyme trios maintain the chromatin-based GPS and guide RNAPII transcription.